2014
DOI: 10.1188/14.cjon.e93-e96
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin: The Need for Exposure Precautions

Abstract: Ribavirin is used in the treatment of respiratory syncytial virus (RSV) in high-risk patients, including patients who have undergone hematopoietic stem cell transplantation, to reduce mortality from RSV pneumonia. It is classified as a hazardous drug with potential for carcinogenicity and teratogenicity. Very few recent studies have examined the risk of exposure, and recommendations for exposure precautions are lacking. Administration should include the use of personal protective equipment and terminal cleanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Although specific anti-viral medications are only available for a limited number of CARV, the decision to administer adjunctive therapy or inhaled ribavirin is complicated by issues of cost, physical isolation of patients, potential aggravation of respiratory symptoms, and concerns of teratogenicity among healthcare personnel. 26,27 The finding that infections caused by adenovirus and parainfluenza virus were more likely to progress to CLAD is probably because these viruses were more often associated with viral pneumonia when encountered. We were not able to statistically demonstrate this for Coxsackie/echovirus group, but we suspect the association with CLAD is being driven by a subpopulation of the viruses detected with this PCR reaction, thereby diminishing our ability to see an association with viral pneumonia in this viral group.…”
Section: Discussionmentioning
confidence: 99%
“…Although specific anti-viral medications are only available for a limited number of CARV, the decision to administer adjunctive therapy or inhaled ribavirin is complicated by issues of cost, physical isolation of patients, potential aggravation of respiratory symptoms, and concerns of teratogenicity among healthcare personnel. 26,27 The finding that infections caused by adenovirus and parainfluenza virus were more likely to progress to CLAD is probably because these viruses were more often associated with viral pneumonia when encountered. We were not able to statistically demonstrate this for Coxsackie/echovirus group, but we suspect the association with CLAD is being driven by a subpopulation of the viruses detected with this PCR reaction, thereby diminishing our ability to see an association with viral pneumonia in this viral group.…”
Section: Discussionmentioning
confidence: 99%
“…These may offer additional economic benefit and offset the cost of CSTD usage. [34][35][36][37][38] A Cochrane review on CSTD with safe handling vs safe handling was released in 2018. 39 The review makes reference to a number of studies that examined the effects on workplace contamination with the introduction of a CSTD, whilst a limited number attempted to address operator exposure by measuring urine levels of cytotoxic drugs.…”
Section: Closed-system Transfer Devices (Cstds)mentioning
confidence: 99%
“…[20][21][22][23] Studies have found that most work surfaces in areas where cytotoxic drugs are handled are contaminated with the drugs. 12,13,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] In studies from several countries, working surfaces of biological safety cabinets, counter tops, floors, equipment and other surfaces have been shown to be contaminated.…”
Section: Occupational Exposurementioning
confidence: 99%
“…However, the effectiveness of ribavirin is extremely limited, and it has more additional side effects. For example, it may cause hemolytic anemia (Krilov, 2011;Mooney et al, 2014). Therefore, it is important to identify good therapeutic strategies to treat the inflammation and lung tissue damage caused by RSV.…”
Section: Introductionmentioning
confidence: 99%